In-office bleaching effects on the pulp flow and tooth sensitivity – case series - Andrés Felipe CARTAGENA; Sibelli Olivieri PARREIRAS; Alessandro Dourado LOGUERCIO; Alessandra REIS; Nara Hellen CAMPANHA (Brazilian Oral Research, 2015)
Laser Doppler flowmetry (LDF) is a noninvasive method capable of evaluating variations in pulp blood flow (PBF) and pulp vitality. This method has thus far not been used to assess changes in blood flow after in-office bleaching. The aim of this case series report was to measure changes in PBF by LDF in the upper central incisor of three patients submitted to in-office bleaching. The buccal surfaces of the upper arch were bleached with a single session of 35% hydrogen peroxide gel with three 15-min applications. The color was recorded using a value-oriented Vita shade guide before in-office bleaching and one week after the procedure. The tooth sensitivity (TS) in a verbal scale was reported, and PBF was assessed by LDF before, immediately, and one week after the bleaching session. The lower arch was submitted to dental bleaching but not used for data assessment. A whitening degree of 3 to 4 shade guide units was detected. All participants experienced moderate to considerable TS after the procedure. The PBF readings reduced 20% to 40% immediately after bleaching. One week post-bleaching, TS and PBF were shown to be equal to baseline values. A reversible decrease of PBF was detected immediately after bleaching, which recovered to the baseline values or showed a slight increase sooner than one week post-bleaching. The LDF method allows detection of pulp blood changes in teeth submitted to in-office bleaching, but further studies are still required.